The Importance of Selecting Appropriate Rotation and Tank-Mix Partners for Novel SDHIs to Enhance Botrytis Fruit Rot Control in Strawberry - Amiri, Achour (Plant disease, 2019)
Botrytis fruit rot (BFR), caused by the necrotrophic fungus Botrytis cinerea, is the most important disease of strawberry and is mainly controlled by applications of fungicides from multiple chemical groups. To develop more effective and sustainable BFR management programs, field trials were conducted to evaluate the efficacy of fluopyram and penthiopyrad, two newly registered succinate dehydrogenase inhibitors (SDHIs), rotated or tank mixed with the multisites thiram and captan or the single-sites fludioxonil and fenhexamid. The treatments were applied at two different strawberry fields during the 2013-14 and 2014-15 seasons. Overall, tank mixtures of fluopyram and penthiopyrad increased yield and reduced BFR better than rotations with the same fungicides. The multisite thiram tank mixed with fluopyram reduced BFR incidence by 63 to 86% versus 56 to 84% when the two fungicides were rotated. Thiram tank mixed with penthiopyrad reduced BFR incidence by 55 to 72% versus 42 to 66% when rotated. Captan rotated or tank mixed with fluopyram had a positive effect on yield and BFR incidence, whereas the combination of captan with penthiopyrad had negative impacts. Similarly, the single-site fenhexamid had significant positive impacts when rotated or tank mixed with fluopyram but resulted in poor BFR control when combined with penthiopyrad. The rotation of fludioxonil with both SDHIs had a significant positive effect, although its combination with fluopyram was more effective. The multirotation consisting of both SDHIs and different multi- and single-site fungicides did not provide a greater efficacy than the dual rotation or tank-mixture programs. Our findings suggest more scrutiny is needed when recommending tank-mixture or rotation partners for new fungicides to ensure compatibility and enhanced BFR management. Future recommendations should emphasize the importance of such selections at an early stage for delaying fungicide resistance development and extending the lifespan of at-risk fungicides